Complex Tuberculous Meningitis: A Case Series Highlighting Rare Co-infections and Severe Complications - Nandlal Kumar; Saumya Singh; Rajan Pathak; Pratima Kumari; Devesh Sharma; Brijnandan Singh (International Journal of Pathogens, 2024)
This case series presents two complex cases of tuberculous meningitis (TBM) with different complications, illustrating the diverse clinical presentations and management challenges of this disease. Case 1 involves an 18-year-old female with TBM complicated by cryptococcal co-infection, while Case 2 describes a 64-year-old female with TBM complicated by obstructive hydrocephalus and secondary bacterial infections. Both patients had been on anti-tubercular therapy before presentation. Diagnostic approaches included cerebrospinal fluid analysis, cultures, and molecular testing. Management strategies varied based on complications, involving antifungal therapy in Case 1 and neurosurgical intervention in Case 2. Outcomes differed significantly, with Case 1 showing complete symptom resolution and Case 2 resulting in mortality despite aggressive treatment. These cases underscore the importance of maintaining high suspicion for TBM, even in patients on anti-tubercular therapy, and the need for comprehensive diagnostic approaches and tailored treatment strategies. They highlight the potential for severe complications and the complexity of managing TBM.
Keywords: Complications; Tuberculous; co-infection; meningitis; treatment